2019
DOI: 10.1017/s0272263119000585
|View full text |Cite
|
Sign up to set email alerts
|

Russian Phono-Lexical Acquisition and Orthographic Input

Abstract: We investigated how grapheme familiarity and grapheme-phoneme correspondence (GPC) congruence affect adult learners’ ability to make use of orthographic input (OI) during phono-lexical acquisition. Native English speakers, with no Russian experience (naïve) or learners of Russian, heard auditory forms, saw pictured meanings, and saw written input either in a No Orthography condition or an Orthography condition for words that contained unfamiliar Cyrillic graphemes, familiar graphemes and congruent GPCs, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, it is less clear how this concept relates to learners with varying script familiarity and literacy experiences across writing systems. Some studies have looked at degree of familiarity, based on similarity between L1 and L2 graphemes in Latin and Cyrillic scripts (Mathieu 2016;Showalter 2018) and L1 English speakers' L2 experience in Russian and Mandarin (Showalter 2020;Hao and Yang 2021;Hayes-Harb and Hacking 2015). However, it continues to be difficult to tease apart script familiarity from broader L2 proficiency, and the overrepresentation of L1 English monolingual samples is noteworthy.…”
Section: Orthographic Influence On L2 Phonological Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is less clear how this concept relates to learners with varying script familiarity and literacy experiences across writing systems. Some studies have looked at degree of familiarity, based on similarity between L1 and L2 graphemes in Latin and Cyrillic scripts (Mathieu 2016;Showalter 2018) and L1 English speakers' L2 experience in Russian and Mandarin (Showalter 2020;Hao and Yang 2021;Hayes-Harb and Hacking 2015). However, it continues to be difficult to tease apart script familiarity from broader L2 proficiency, and the overrepresentation of L1 English monolingual samples is noteworthy.…”
Section: Orthographic Influence On L2 Phonological Acquisitionmentioning
confidence: 99%
“…Thus, incongruence was a pervasive effect, regardless of perceptibility, whereas the unfamiliarity of orthographic input did not pose additional challenges. Showalter (2020) extended this study to compare naïve, beginner, and experienced learners, as well as the impact of explicit instruction. Interference effects from incongruent GPCs were particularly evident with the naïve participants, which did not improve with instruction, but these interference effects reduced with increased language experience.…”
Section: Naïve Participantsmentioning
confidence: 99%
“…With an eye to the practical implications of this line of research, Showalter (2018b) and Showalter (2019) followed up on this finding, investigating the effects of L2 experience and instructional interventions on the Cyrillic incongruency effect for native English speakers. A new group of naive native speakers of English were assigned to the no orthography, orthography, intervention A, and intervention B groups ( n = 20 in each group).…”
Section: Orthography and The Pronunciation And Recognition Of L2 Wordsmentioning
confidence: 99%
“…However, we have very little empirical evidence so far in this regard. A study that has observed improvement over time by learners is presented in Showalter (2018b) and Showalter (2020), which found that experienced L1 English learners of Russian had overcome the interference of incongruent orthographic effects to some extent relative to beginning learners and naive participants.…”
Section: Research Summary and Pedagogical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation